PENGELOMPOKKAN DAERAH IRIGASI DI KABUPATEN SLEMAN BERDASARKAN INDEKS KINERJA DAERAH IRIGASI MENURUT PERATURAN MENTERI PU NOMOR 32/PRT/M/2007 DENGAN METODE FUZZY CLUSTERING - , FAUZIZAH PUTRI SUDIRO, Murtiningrum, STP, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
improve its service. In addition, irrigation system performance assessment can be used as consideration in making policy on irrigation. Site specific policy may be well implemented in an irrigation system. However, in the district with a lot of irrigation systems, it may be impossible to develop a policy for each irrigation system. The main objective of this research is to assess irrigation systems performance in several irrigation systems and cluster them based on their performances. The research was conducted in 18 irrigation systems which were located in the Sleman District, Yogyakarta. The evaluation is done based on the irrigation system performance index form (form 1) according to the regulation of the ministry of public work number 32/2007 on the operation and maintenance of irrigation systems. To irrigation systems was then clustered using fuzzy clustering method that is Fuzzy C-Means together with the assist of MATLAB 5.3 software. The result of irrigation system performance evaluation showed that 7 irrigation systems had inadequate performance index and needed more maintenance concern. On the other hand, 11 irrigation systems had good performance. Fuzzy clustering fot the 18 irrigation systems resulted that (a) the first cluster consisted of Pule, Sigedangan, Randu (Banjarharjo), Jering, and Plumbangan Irrigation Systems